ETIKA BISNIS DALAM KONTRAK BANK ISLAM - Riky Soleman (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2023)
Islam is a perfect religion that includes and regulates all aspects of human life (syumul). Today, there is a tendency to re-ground Islamic religious values ÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Â¹ÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Â¹in every aspect of human life. The awareness of the people to carry out Islamic teachings correctly and completely (kÃƒâ€žÃ‚Âffah) appears. This awareness emerges starting from the understanding of Islam as a universal teaching, not only touching the spiritual-ritual aspect, but also touching aspects of life broadly, including the economy. In Islamic economics, business and ethics must be seen as two contradictory things, because business which is a symbol of the mundane is also considered as an integral part of matters that are hereafter. That is, if the orientation of business and investment efforts in the afterlife (intended as worship and is the totality of obedience to God), then business by itself must be in line with moral principles based on faith in the hereafter.